A numerical study into effects of soil compaction and heat storage on thermal performance of a Horizontal Ground Heat Exchanger. (July 2021) - Tang, F.; Lahoori, M.; Nowamooz, H.; Rosin-Paumier, S.; Masrouri, F.
Abstract: The good capacity of the numerical simulations makes possible to bring some further responses on the backfill soil selection and its installation depth in the Horizontal Ground Heat Exchanger (HGHE). Therefore, a well-known backfill soil was considered to be used as substitutive material. The hydrothermal properties of the backfill material were estimated in laboratory and then injected in a numerical framework considering the atmosphere-soil-HGHE interaction. Numerical simulations were performed for a HGHE installed in the compacted backfill soil and the local natural soil. The simulation results showed that the compacted backfill soil improves by 8.5 % the HGHE performance compared to local uncompacted soil. Two heat storage scenarios at three different installation depths were also investigated. The results showed that an inlet fluid temperature of 50 ° C in summer increased highly the system performance by 13.7 % –41.4 %, while the improvement was less significant (0 % –4.8 % ) for the ambient inlet temperature scenario. A deeper installation depth of HGHE increased also the system performance, the more energy could be stored and extracted. Highlights: A numerical framework considering the atmosphere-soil interaction was considered. The performance of a slinky-type Horizontal Ground Heat Exchanger was evaluated. Horizontal Ground Heat Exchanger installed in the compacted backfill soil. The compacted backfill soil improves 8.5% the system performance. An inlet fluid of 50 °C in summer increases highly the system performance.